2018
DOI: 10.1161/circoutcomes.118.004818
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Postoperative Pneumonia and 90-Day Episode Payments and Outcomes Among Medicare Beneficiaries Undergoing Cardiac Surgery

Abstract: Background Postoperative pneumonia is the most common healthcare-associated infection in cardiac surgical patients, yet their impact across a 90-day episode of care remains unknown. Our objective was to examine the relationship between pneumonia and 90-day episode payments and outcomes among Medicare beneficiaries undergoing cardiac surgery. Methods and Results Medicare claims were used to identify beneficiaries with episodes of coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The occurrence of postoperative pneumonia significantly increased mortality, length of stay, and early hospital readmission for all patients. 100 In both cohorts, hospitals with high pneumonia rates had higher costs and inferior clinical outcomes as compared to hospitals with low pneumonia rates. 100 These findings were consistent with previous evidence suggesting that postoperative infections significantly contribute to excessive healthcare spending.…”
Section: Postoperative Pneumonia-impact On Cost and Outcomesmentioning
confidence: 94%
See 4 more Smart Citations
“…The occurrence of postoperative pneumonia significantly increased mortality, length of stay, and early hospital readmission for all patients. 100 In both cohorts, hospitals with high pneumonia rates had higher costs and inferior clinical outcomes as compared to hospitals with low pneumonia rates. 100 These findings were consistent with previous evidence suggesting that postoperative infections significantly contribute to excessive healthcare spending.…”
Section: Postoperative Pneumonia-impact On Cost and Outcomesmentioning
confidence: 94%
“…100 In both cohorts, hospitals with high pneumonia rates had higher costs and inferior clinical outcomes as compared to hospitals with low pneumonia rates. 100 These findings were consistent with previous evidence suggesting that postoperative infections significantly contribute to excessive healthcare spending. 101 The investigators suggested that focused efforts to reduce postoperative pneumonia in cardiac surgery may both improve outcomes and reduce costs.…”
Section: Postoperative Pneumonia-impact On Cost and Outcomesmentioning
confidence: 94%
See 3 more Smart Citations